Towards a New Catholic Church in Advanced Modernity: Transformations, Visions, Tensions, red. S. Hellemans, J. Wissink, Zürich−Berlin 2012, ss. 280, Tilburg Theological Studies, t. 5. - Maciążek, Wojciech (Teologia w Polsce, 2020)
Recenzja książki: Towards a New Catholic Church in Advanced Modernity: Transformations, Visions, Tensions, red. S. Hellemans, J. Wissink, Zürich−Berlin 2012, ss. 280, Tilburg Theological Studies, t. 5.